1996
DOI: 10.1007/bf00227958
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the hippocampal formation by vestibular stimulation: a functional magnetic resonance imaging study

Abstract: Functional MRI (f-MRI) is a non-invasive technique developed to permit functional mapping of the brain with a better temporal and spatial resolution than that offered by PET techniques. In our study, f-MRI was performed using blood oxygenation level dependent (BOLD) contrast imaging based on the magnetic properties of hemoglobin. This method relies on changes in the blood supply to the brain that accompany sensory stimulation or changes in cognitive state. All the images were obtained at 1.5 T on a Signa GEMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
1
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 17 publications
6
118
1
6
Order By: Relevance
“…Congruently, epileptic patients with vestibular aurae suffer from lesions surrounding the superior temporal gyrus and the temporoparietal cortex [99,107]. This location has also been confirmed by functional neuroimaging studies in healthy subjects using caloric and galvanic stimulation of the peripheral vestibular system revealing unanimously predominant activations centered on the TPJ and insula [6,19,20,32,39,46,47,50,51,70,72,85,94,95,110,112,118] with activations in the superior temporal gyrus, posterior insula, inferior parietal lobule (angular and supramarginal gyri), and postcentral gyrus. Although many regions surrounding the TPJ/insula have been found activated, opinions concerning the exact location of the human homologue of the PIVC differ (Fig.…”
Section: The Vestibular Cortexmentioning
confidence: 80%
See 1 more Smart Citation
“…Congruently, epileptic patients with vestibular aurae suffer from lesions surrounding the superior temporal gyrus and the temporoparietal cortex [99,107]. This location has also been confirmed by functional neuroimaging studies in healthy subjects using caloric and galvanic stimulation of the peripheral vestibular system revealing unanimously predominant activations centered on the TPJ and insula [6,19,20,32,39,46,47,50,51,70,72,85,94,95,110,112,118] with activations in the superior temporal gyrus, posterior insula, inferior parietal lobule (angular and supramarginal gyri), and postcentral gyrus. Although many regions surrounding the TPJ/insula have been found activated, opinions concerning the exact location of the human homologue of the PIVC differ (Fig.…”
Section: The Vestibular Cortexmentioning
confidence: 80%
“…These regions represent probably the human homologue of two monkey areas that have been found to integrate vestibular and somatosensory information: area 2v, at the base of the intraparietal sulcus [53] and area 3av at the hand/arm and neck/trunk representations [66,96]. Another vestibular area has been described in the posterior parietal cortex and was activated during caloric and galvanic vestibular stimulations particularly in the intraparietal sulcus [50,85,112] and superior parietal lobule [118]. These regions are likely homologous to monkey area 7 [82] and the ventral and medial intraparietal areas [27,77] receiving vestibular information as well as visual, somatosensory and auditory cues.…”
Section: The Vestibular Cortexmentioning
confidence: 97%
“…Vestibular input to the hippocampus may update spatial representations as the animal moves, so that the representations reflect current body position (McNaughton et al, 1996;Smith, 1997). Vestibular stimulation activates the hippocampal formation, parietal cortex, and retrosplenial cortex in humans (Vitte et al, 1996) and rats (Horii et al, 1994), and modulates primate hippocampal neuronal activity (O'Mara et al, 1994). Vestibular stimulation modulates rat hippocampal place cell activity (Sharp et al, 1995;Wiener et al, 1995;Bures et al, 1997), hippocampal theta rhythm (Gavrilov et al, 1995), and HD cell activity Blair and Sharp, 1996).…”
Section: Vestibular-hippocampal Interactionmentioning
confidence: 99%
“…Therefore, internal self-motion cues also play an important role in influencing the spatial firing properties of hippocampal neurons (Foster et al, 1989;Taube and Burton, 1995;Knierim et al, 1998). Indeed, vestibular stimulation activates the hippocampal formation (Horii et al, 1994;Vitte et al, 1996), influences hippocampal place cell activity (Sharp et al, 1995), and influences navigation in humans (Telford et al, 1995). Finally, lesions of the vestibular apparatus abolish the directional firing of anterior thalamic neurons and impair spatial memory, as outlined above.…”
Section: Introductionmentioning
confidence: 95%
“…Relatively few previous studies have investigated vestibular-cognitive interactions in patients with vestibular disorders, yet relevant literature is growing (for a review see Smith et al 2005;Hanes and McCollum 2006;Borel et al 2008). In this context, it is noteworthy that vestibular sensory information is processed in the central vestibular system including the vestibular nuclei, parts of the cerebellum and the thalamus (Chen-Huang and McCrea 1999;McCrea and Luan 2003;Dieterich and Brandt 2008), along with various cortical regions including the insula and parts of the temporal, parietal, and frontal lobes (Brandt and Dieterich 1999;de Waele et al 2001;Emri et al 2003), and the hippocampus (Vitte et al 1996). Clinical studies revealed impaired performance of vestibular patients in spatial tasks such as spatial perception (Bohmer and Mast 1999a, b;Clement et al 2009), spatial memory, and navigation (Schautzer et al 2003;Brandt et al 2005;Peruch et al 2005).…”
Section: Introductionmentioning
confidence: 99%